PENERAPAN GOOD GOVERNANCE, TOTAL QUALITY MANAGEMENT, LOCUS OF CONTROL, TIME BUDGET PRESSURE SEBAGAI PREDIKTOR KINERJA AUDITOR INTERNAL - Rahayu Widasari, Dewa Ayu; Ariyanto, Dodik (E-Jurnal Akuntansi; Vol 18 No 1 (2017), 2017)
This study aimed to analyze the effect of the application of good governance, total quality management, locus of control, time budget pressure as a predictor performance of internal auditors. This research was conducted at the office of PT. Bank BRI Regional Office Denpasar that has thirteen branch offices with 65 of internal auditors as samples through the method of sample saturated. The data collection is done by distributing questionnaires and analyzed with multiple linear regression techniques. Test Results f variable implementation of good governance, total quality management, locus of control, time budget pressure effect on the performance of internal auditors. T test results showed that good governance, total quality management, locus of control has positive influence on the performance of internal auditors, while the time budget pressure negatively affect the performance of internal auditors at Bank BRI Regional Office of Denpasar.
Keywords: Good Governance, Total Quality Management, Locus Of Control, Time Budget Pressure, Performance Auditor